2019
DOI: 10.24259/fs.v3i1.5982
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the determining factors of recreation demand in Kongar Lake of South Sumatera: An individual travel cost approach

Abstract: Assessing the economic value of natural resources is always challenging and depends on various perspectives. Specifically, this study seeks to identify the determining factors of recreation demand regarding the Kongar Lake of South Sumatera. The data was obtained from a survey of 150 individuals who visited the lake. The approach used descriptive statistics and an individual travel cost method (ITCM) to conduct the investigation of distributional effects across variables on the number of visitors by using a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Moreover, conservation education also needs to be provided to visitors through learning, raising awareness, and motivations on the environment in an effort to prevent damaging the tourist site. This is in line with the findings of [45] that improving the quality of environmental services has the ability to increase the number of visitors and the willingness to pay in Lake Kongar even though there are several other influential factors such as cost, visitor's characteristics, work, distance to the lake and others.…”
Section: The Role Of Urban Forests In Environmental Conservationsupporting
confidence: 88%
“…Moreover, conservation education also needs to be provided to visitors through learning, raising awareness, and motivations on the environment in an effort to prevent damaging the tourist site. This is in line with the findings of [45] that improving the quality of environmental services has the ability to increase the number of visitors and the willingness to pay in Lake Kongar even though there are several other influential factors such as cost, visitor's characteristics, work, distance to the lake and others.…”
Section: The Role Of Urban Forests In Environmental Conservationsupporting
confidence: 88%
“…On the other hand, the annual trip frequency at Lake Tana and other sites was found to be similar. For example, findings from Kongar Lake in Indonesia (61.3%) [87] and Nagarhole National Park and Nandi Hills in India (70%) [86] revealed that the visitors only made a single visit.…”
Section: Determinants Of Recreation Demand/tripmentioning
confidence: 99%
“…Rather than examining the particular earnings of a given commodity, Suhel et al (2019) use a payment for ecosystem services approach to estimating the potential economic benefits from recreation at Kongar Lake. The analysis looks at tourism potential in Kongar Lake more broadly, as a way of making the case for protecting natural resources as recreation destinations in South Sumatra (Suhel et al, 2019). The analysis also focuses much more on the consumer side, highlighting the various factors that visitors consider as determinants for their continued recreation at these sites.…”
Section: The Economiesmentioning
confidence: 99%